Ciprofloxacin-Associated Stevens-Johnson Syndrome in A Healthy Young Woman: A Case Report - Grady; Dewa Ayu Putu Mitha Paramitha Rahayu; Ida Ayu Uttari Priyadarshini (International Medical Journal Corp. Ltd, 2025)
Background: Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) are rare but life-threatening mucocutaneous reactions, primarily triggered by medications. These conditions are characterized by extensive epidermal necrosis, mucosal involvement, and systemic complications. Ciprofloxacin, a fluoroquinolone antibiotic, is an uncommon but recognized cause of SJS. Early recognition and multidisciplinary management are crucial in reducing morbidity and mortality. Case Presentation: We report a case of a previously healthy 23-year-old woman who developed SJS following ciprofloxacin use. The patient presented with widespread erythematous patches, blistering lesions, mucosal erosions, ocular involvement, and urogenital ulcerations. The SCORTEN score was calculated to be 2, indicating an estimated mortality risk of 12.1%. Management included immediate discontinuation of the suspected causative drug, systemic corticosteroids, wound care, fluid and electrolyte balance maintenance, and supportive ophthalmologic and urologic treatments. The patient demonstrated clinical improvement and was discharged after a 11-day hospital stay. Conclusion: This case highlights the potential for ciprofloxacin to induce SJS, emphasizing the need for vigilance in drug-induced cutaneous reactions, even in younger patients. Prompt diagnosis, drug withdrawal, and comprehensive supportive care play pivotal roles in patient outcomes. Given the unpredictability of long-term sequelae, continued monitoring is essential.